2020
DOI: 10.35371/aoem.2020.32.e35
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between long work hours and self-reported sleep disorders of non-shift daytime wage workers in South Korea: data from the 5th Korean Working Conditions Survey

Abstract: Background: Studies have investigated the relationship between long work hours and sleep disorders; however, they have focused on shift workers or specific workers who are at high risk of industrial accidents rather than wage workers in general. The purpose of this study is to investigate the effects of long work hours on sleep disorders among non-shift daytime wage workers. Methods: We conducted a secondary analysis of data from the 5th Korean Working Conditions Survey. From the 50,205 total participants, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…The multiple logistic regression model employed in this study demonstrated that long work hours, quick return to work, having to come to work on short notice, and changes in one’s work schedule were each statistically significantly associated with sleep disturbance among the surveyed healthcare professionals. Moreover, in our supplementary analysis, we found that total working hours per week was a statistically significant predictor for sleep problems in both European countries and in Korea, which was consistent with the results of previous studies [ 45 , 46 ]. We note that the results in European countries were consistent with previous findings demonstrating that long work shifts (> 12 h), long work hours per week, and a quick return to work were associated with increased sleepiness (which can lead to adverse outcomes for healthcare workers and for patients) [ 25 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…The multiple logistic regression model employed in this study demonstrated that long work hours, quick return to work, having to come to work on short notice, and changes in one’s work schedule were each statistically significantly associated with sleep disturbance among the surveyed healthcare professionals. Moreover, in our supplementary analysis, we found that total working hours per week was a statistically significant predictor for sleep problems in both European countries and in Korea, which was consistent with the results of previous studies [ 45 , 46 ]. We note that the results in European countries were consistent with previous findings demonstrating that long work shifts (> 12 h), long work hours per week, and a quick return to work were associated with increased sleepiness (which can lead to adverse outcomes for healthcare workers and for patients) [ 25 , 47 , 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Long working hours, sleep disturbance and burnout are key factors that deteriorate workers' quality of life. Previous studies have suggested that exposure to long working hours is an independent risk factor for sleep disturbance [7][8][9][10] and burnout [11][12][13] among workers. However, although some studies have revealed associations between long working hours and sleep disturbance and burnout, the mechanism underlying these relationships is yet to be fully elucidated.…”
Section: Long Working Hours Work-family Conflict and Mental Healthmentioning
confidence: 99%
“…29 The Korean Working Conditions Survey (KWCS) is a benchmark of the European Working Condition Survey (EWCS) and the Labor Force Survey (LFS) of the United Kingdom; it was designed to assess the overall work environment, such as the pattern of work, the type of work employment, occupation, industry, exposure to risk factors, and the stability of employment. 30 The KWCS is a cross-sectional study that is regularly administered by the Korea Occupational Safety and Health Agency (KOSHA). [31][32][33][34][35]…”
Section: Nature Of the Studymentioning
confidence: 99%